2019
DOI: 10.1109/jbhi.2018.2790951
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Criteria Decision Analysis-Based Multifactor Dimensionality Reduction for Detecting Gene–Gene Interactions

Abstract: Gene-gene interactions (GGIs) are important markers for determining susceptibility to a disease. Multifactor dimensionality reduction (MDR) is a popular algorithm for detecting GGIs and primarily adopts the correct classification rate (CCR) to assess the quality of a GGI. However, CCR measurement alone may not successfully detect certain GGIs because of potential model preferences and disease complexities. In this study, multiple-criteria decision analysis (MCDA) based on MDR was named MCDA-MDR and proposed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…However, we found that some SNP combinations (dominated solutions) that are eliminated during the search by the nondominated solutions are the true disease-causing SNP combinations, which results in an increase in the number of false negative errors. In FHSA-SED [40], NHSA-DHSC [41] and MCDA-MDR [73], the experimental results indicate that multicriteria algorithms are superior to multi-objective optimization algorithms. In future studies, lightweight and complementary evaluation criteria should also be considered to screen for suspected SNP interactions that have a strong association with disease status using any SIS in the first search phase.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that some SNP combinations (dominated solutions) that are eliminated during the search by the nondominated solutions are the true disease-causing SNP combinations, which results in an increase in the number of false negative errors. In FHSA-SED [40], NHSA-DHSC [41] and MCDA-MDR [73], the experimental results indicate that multicriteria algorithms are superior to multi-objective optimization algorithms. In future studies, lightweight and complementary evaluation criteria should also be considered to screen for suspected SNP interactions that have a strong association with disease status using any SIS in the first search phase.…”
Section: Discussionmentioning
confidence: 99%
“…We model the epistasis process as a one-step Markov Decision Process (MDP) (Figure 1). The state S is a latent representation encoded from genome data; The action space is all the SNPs, where highly interacted SNPs are selected by a probability threshold so that it poses no constraint to fix the size of interaction; the reward is efficient interaction measurements like MDR correct classification rate (CCR) and Rule Utility (Yang et al, 2018). A reinforcement learning agent will learn to select SNPs that have high rewards, i.e., high interaction, by using the policy gradient method.…”
Section: Modelmentioning
confidence: 99%
“…Now, we can calculate the two measures. These two measures together are shown to be effective in measuring epistasis (Yang et al, 2018). MDR CCR is the correct classification rate and Rule Utility U derives from the chi-square statistics of rule relevance, which measures the interaction:…”
Section: Rewardmentioning
confidence: 99%
See 1 more Smart Citation
“…The multifactor dimensionality reduction (MDR) method is a novel computational approach initially developed for detecting complex multifactor interactions. 12 Several new MDR-based methods, such as generalized MDR, 13 classification based MDR, 14 balanced MDR, 15 multi-objective MDR, 6,17 and other approaches have been proposed for improving the performance and applicability of the general MDR method. Evenly distributed case-control data sets are required for general MDR-based analyses.…”
Section: Introductionmentioning
confidence: 99%